Abdominal Stretching Relieves Dysmenorrhea in Home Industry Workers - Prasetyowati; Yoga Tri Wijayanti; Septi Widiyanti; Martini (Formosa Journal of Sustainable Research, 2022)
Dysmenorrhea can have an impact that affects women's activities, this problem bothers at least 50% of women of reproductive age and 60-85% in their teens. This research was conducted to determine the effectiveness of abdominal stretching in reducing menstrual pain (dysmenorrhea) in women of childbearing age. The research design used was the Pre-Experiment with One Group Pretest Posttest design. Sampling in this study using purposive sampling technique. The samples used in this study totaled 32 WUS samples of Kelanting home industry workers and filter and border craftsmen in East Lampung Regency which were conducted in 2019. The results of the study showed that abdominal stretching had an effect on reducing menstrual pain